Efficient production of glycosylated and non-glycosylated mycobacterium tuberculosis antigen 85B fused to PVX coat protein in Nicotiana benthamiana plants - González, Pablo A. (2018)
The development of alternative subunit based-vaccines against tuberculosis is necessary due to variable efficiency and some security concerns of the BCG vaccine. The aim of this work was evaluate the production of the Mycobacterium tuberculosis Ag85B antigen fused to Potato Virus X Coat Protein (PVX-CP) by transient expression in Nicotiana benthamiana for subunit-based tuberculosis vaccine formulation. A codon-optimized M. tuberculosis Ag85B gene was fused to PVX-CP and expressed both as a full length precursor and as a mature version lacking the leader peptide. Signal peptides of N. tabacum genes were added to precursor and mature Ag85B-CP to compare the efficiency of cytoplasmic and apoplastic expression. Constructs were agroinfiltrated into N. benthamiana leaves and the yield and integrity of recombinant proteins were analysed. Glycosylation status was determined by treatment with peptide N-glycosidase F. The highest amounts of fusion protein were obtained by expressing mature Ag85B lacking its leader sequence directed to the apoplast, which reached a yield of 100 mg of antigen per kg of fresh leaf. Glycosylated and non-glycosylated fusion proteins were obtained in the apoplastic and cytoplasmic space, respectively. We showed the feasibility of producing Ag85B-CP protein in N. benthamiana leaves for application as a subunit vaccine and demonstrated the importance of expressing mature Ag85B to increase yield and to avoid the production of degraded protein fragments unsuitable for a pharmaceutical product.